The green attraction: mediating role of environmental CSR and green HRM in the relationship between green culture and organizational attractiveness - Comert, Perlin Naz; Ozer, Elif; Gurol, Yonca; Akan, Gizem; Bulgur, Nazli Ece (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study aims to examine the mediating role of green human resources management (GHRM) and environmental corporate social responsibility (ECSR) in the relationship between organizational green culture (OGC) and organizational attractiveness (OA).Design/methodology/approachThe study used an explanatory sequential mixed-methods design. Survey data of 544 employees from 281 firms was analyzed using SPSS, Amos and PROCESS Macro. Qualitative data was collected through interviews with 13 human resources professionals.FindingsResults indicated that OGC impacts OA through GHRM and ECSR. Interview findings supported the quantitative results. Also, qualitative results extended the quantitative results by revealing that organizational pride, commitment, satisfaction, motivation and work meaningfulness have the potential to be underlying mechanisms in the impact of ECSR on OA. In addition, interview findings emphasized that for Generation Z, ECSR and GHRM are important factors for increasing OA.Originality/valueThis study strengthens social identity theory by using mixed-method design to reveal how GHRM and ECSR can be significant factors in the relationship between OGC and OA. Using a qualitative study extends the understanding of the quantitative results and proposes fruitful topics for future research.
Keywords: Green human resource management; Organizational green culture; Organizational attractiveness; Environmental corporate social responsibility; CORPORATE SOCIAL-RESPONSIBILITY; HUMAN-RESOURCE MANAGEMENT; KNOWLEDGE MANAGEMENT; MODERATING ROLE; RECRUITMENT; CONTEXT; PRODUCT; DESIGN; TALENT; IMPACT; Business & Economics